Predpisi za pripravke tkivnega inženirstva in za somatsko celično zdravljenje - Puhar, Saša (Farmacevtski vestnik, 2005)
Tissue engineering is a new and rapidly developing interdisciplinary field of biotechnology, dealing with tissues and organs by applying viable cell-, tissue- and organotypic cultures prepared in vitro. Somatic cell therapy is a part of tissue engineering and it encompasses preparation of viable human cells, cultured ex vivo in a way to achieve sufficient number of cells suitable for the re-implantation into recipient. Beside wanted effect, the application of human cells and tissues may cause transferable diseases and other unwanted effects in the patient. Risk estimation for the recipient is therefore the main criteria for their application. Transmission of infectious diseases thus represents the major threat., along with possible contamination ot cell cultures and the loss of specific cell characteristics occurring during their in vitro manipulation. Due to the complexity of tissue engineeredmedical products and the lack of clinical experience following theirapplication it is necessary to thoroughly regulate this field in order toassure quality, safety and effectiveness.
Keywords: Biotechnology; Biotehnologija; Celične kulture; Cells, Cultured; Kvaliteta, nadzor; Quality Control; somatske celice; Tissue Therapy; tkivno in\enirstvo; Tkivno zdravljenje